Risk-associations between HLA-DPB1 T cell epitope matching and outcome of unrelated hematopoietic cell transplantation are independent from HLA-DPA1 - Fleischhauer, Katharina (2014)
HLA-DP antigens are beta-alpha heterodimers encoded by polymorphic HLA-DPB1 and -DPA1 alleles, respectively, in strong linkage disequilibrium (LD) with each other. Non-permissive unrelated donor (UD)-recipient HLA-DPB1 mismatches across three different T cell epitope (TCE) groups are associated with increased mortality after hematopoietic cell transplantation (HCT), but the role of HLA-DPA1 is unclear. We studied 1281 onco-hematologic patients after 10/10 HLA-matched UD-HCT facilitated by the National Marrow Donor Program. Non-permissive mismatches defined solely by HLA-DPB1 TCE groups were associated with significantly higher risks of treatment-related mortality compared to permissive mismatches (HR 1.30, CI 1.06–1.53; p=0.009) or allele matches. Moreover, non-permissive HLA-DPB1 TCE group mismatches in the graft versus host (GvH) direction significantly decreased the risk of relapse compared to permissive mismatches (HR 0.55, CI 0.37–0.80; p=0.002) or allele matches. Splitting each group into HLA-DPA1*02:01 positive or negative, in frequent LD with HLA-DPB1 alleles from two of the three TCE groups, or into HLA-DPA1 matched or mismatched, did not significantly alter the observed risk associations. Our findings suggest that the effects of clinically non-permissive HLA-DPB1 TCE group mismatches are independent of HLA-DPA1, and that selection of donors with non-permissive DPB1 TCE mismatches in GvH direction might provide some protection from disease recurrence.